2019
DOI: 10.1161/circulationaha.118.039132
|View full text |Cite
|
Sign up to set email alerts
|

Higher Body Mass Index in Adolescence Predicts Cardiomyopathy Risk in Midlife

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…The BMI and DBP levels of CVD patients were significantly higher than those of the healthy volunteers. This result was consistent with previous reports, as BMI and DBP are high risk factors for CVD (2,12,13). The training set included 358 participants from Hebei and Shaanxi (96 HI, 74 stroke, 73 CHD, 65 diabetes, and 50 HBP volunteers).…”
Section: Participant Characteristicssupporting
confidence: 89%
“…The BMI and DBP levels of CVD patients were significantly higher than those of the healthy volunteers. This result was consistent with previous reports, as BMI and DBP are high risk factors for CVD (2,12,13). The training set included 358 participants from Hebei and Shaanxi (96 HI, 74 stroke, 73 CHD, 65 diabetes, and 50 HBP volunteers).…”
Section: Participant Characteristicssupporting
confidence: 89%
“…We and others have demonstrated strong links between body weight in young people and HF and cardiomyopathy later in life [7‐10], where obesity continues to be a strong risk factor for HF also amongst the middle‐aged [11]. In contrast, whilst body weight amongst the young is a strong predictor also for CHD and ischaemic stroke (IS), obesity amongst the middle‐aged, whether expressed as body mass index (BMI) or as abdominal obesity, seems to be less important as predictors over and above blood pressure, diabetes and lipids [12].…”
Section: Introductionmentioning
confidence: 99%
“…HCM-related outcomes) [12]. Moreover, a prospective study in adolescent men demonstrated that even mildly elevated body weight in late adolescence significantly increased the risk to develop dilated cardiomyopathy in adulthood [13]. At the heart level, a recent proteomics study in human HCM tissue samples showed reduced levels of energy metabolism proteins [14].…”
Section: Altered Metabolism As Key Driver Of Disease In Cardiomyopathiesmentioning
confidence: 99%